2021
DOI: 10.1128/jcm.00374-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Quantitative DiaSorin Liaison Antigen Test to Reverse Transcription-PCR for the Diagnosis of COVID-19 in Symptomatic and Asymptomatic Outpatients

Abstract: Background:We evaluated the quantitative DiaSorin Liaison SARS-CoV-2 antigen test in symptomatic and asymptomatic individuals consulting their general practioner (GP) during a period of stable intense virus circulation (213/100,000 habitants per day). Methods:Left-over RT-PCR positive (n=204) and negative (n=210) nasopharyngeal samples were randomly selected among fresh routine samples collected from patients consulting their GP. Samples were tested on Liaison XL according to the manufacturer’s instructions. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
(20 reference statements)
5
16
0
Order By: Relevance
“…As expected, saliva yielded less good performance and should be restricted to settings with limited access to sampling disposable or patients presenting contra-indication for naso-pharyngeal sampling. Comparable results were previously obtained on saliva and on other instruments [68].…”
Section: Discussionsupporting
confidence: 86%
“…As expected, saliva yielded less good performance and should be restricted to settings with limited access to sampling disposable or patients presenting contra-indication for naso-pharyngeal sampling. Comparable results were previously obtained on saliva and on other instruments [68].…”
Section: Discussionsupporting
confidence: 86%
“…between 91 and 100% [5][6][7][8][9][10][11][12][13][14][15][16]. While assay specificities were frequently found to be relatively high [5][6][7][8][9][10][11][12][13][14][15][16], assay sensitivities according to international and national guidelines for rapid Ag tests in general, requiring positive rate percentages ≥ 80, have frequently not been met [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…between 91 and 100% [5][6][7][8][9][10][11][12][13][14][15][16]. While assay specificities were frequently found to be relatively high [5][6][7][8][9][10][11][12][13][14][15][16], assay sensitivities according to international and national guidelines for rapid Ag tests in general, requiring positive rate percentages ≥ 80, have frequently not been met [17,18]. Further, the studies published so far did not compare different automated SARS-CoV-2 Ag assays among each other, which will be critical for diagnostic laboratories seeking to implement such assays.…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity of DiaSorin LIAISON SARS-CoV-2 Ag assay was evaluated to be 75.33% and the specificity reached 100%. Previous investigations of the LIAISON SARS-CoV-2 Ag test showed an overall sensitivity ranging from 31 to 84.8% and specificity of ≈100% at the 200 TCID 50 /mL manufacturer's cut-off [5,[24][25][26], whereas, when applying the cut-off at 82 TCID 50 /mL, a previous report showed that the sensitivity of the DiaSorin LIAISON SARS-CoV-2 Ag test yielded 73% sensitivity [26]. Moreover, similar automated antigenic assays have previously been evaluated and exhibited sensitivity ranging from 70% to 97% [21,22,[27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 96%
“…Simpler and less expensive antigenbased tests have been developed to address these issues. However, antigen-detecting rapid diagnostic tests (Ag-RDT) require a visual readout and lack proper internal quality control, making them more prone to errors [5][6][7]. However, a number of automated antigendetecting diagnostic assays for SARS-CoV-2 detection are now commercially available and can result in rapid decisions on patient care, isolation and contact tracing at the point of care [8].…”
Section: Introductionmentioning
confidence: 99%